Answer:
x= 3, -4
Step-by-step explanation:
Answer:
y = -6x + 3
Step-by-step explanation:
y = -3(2x) -3(-1) = -6x + 3(1) = -6x + 3
Answer:
2x³ + 12x² + 10x - 24
Step-by-step explanation:
(2x² + 6x - 8)(x + 3) Distribute
2x³ + 6x² + 6x² + 18x - 8x - 24 Combine like terms
2x³ + 12x² + 10x - 24 This expression is in standard form
If this answer is correct, please make me Brainliest!
Answer:
he has 472 points now.
Step-by-step explanation:
The answer is D.
You have to make the whole numbers equal to then solve for the exponents:
F(x) means y, therefore, y is 9.
9 = 3^x.
3^2 is the same as 9.
Then, 3^2 = 3^x.
Then solve for the exponents,
2 = x
Therefore your answer is 2.